(untitled) (Research, Society and Development, 2022)
The present work derives from research that approaches the construction of masculinities in the pandemic in dialogue with the spaces of care and community health promotion in a metropolitan city of Rio Grande do Sul. The objective was to discuss the (non) care and access of men in the spheres of health promotion and how masculinities are constructed in this context. The methodology was carried out through the analysis of the National Politics for Integral Attention to Men’s Health (PNAISH) to understand how care spaces for this population occur, and interviews were carried out with health professionals from the Family Health Strategy (ESF), with in order to aggregate and reinforce discussions in the area of male care promotion. The methodological approach was supported by authors who discuss and problematize the productions of masculinities in society and the (non) access of men in spaces of care, above all, through the discussions and concerns that the gender theme proposes. It was then found that the pandemic amplified preexisting inequalities, leaving male constitutions that escape the hegemonic model, in a space of non-care. In addition, the unpreparedness of professionals who work in front of health units was evidenced, which led to further alienating men - especially young, black and low-income men - from these spaces.